Redesain Penampilan Visual Dan Promosi Majalah Sunda Manglé - Harnandy, Stefani Rumanto; Mulyadi, Riki Himawan; Heryadi, Heddy (Serat Rupa: Journal of Design, 2024)
In Indonesia there are many diverse regional languages, one of which is Sundanese. Sundanese is one of the oldest languages in Indonesia and is one of the regional languages that is often used by the people of Indonesia in West Java region/province. However, unfortunately, Sundanese culture and language began to fade with the times, especially among millennials. To preserve Sundanese culture and language a variety of media are used, one of which is Manglé Magazine. The Manglé magazine is the only Sundanese language magazine that has a mission to preserve Sundanese and still survive today. But the lack of interest in millennials to read, study and preserve the magazine is due to the lack of appealing designs, lack of promotion and supporting media. The Governor of West Java for the 2018-2023 period, Ridwan Kamil, encouraged Manglé Magazine to be able to adapt in digital form to attract reading interest, boost literacy culture and help preserve Sundanese culture and language. To achieve this goal redesign and repositioning are needed which include redesign of the cover appearance and contents of the magazine rubric, changes in the target market for millennial young generation, promotion strategies using AISAS theory and supporting media in the form of mobile applications. The creative concept and methodology used in this design was taken from the vision and mission of Manglé Magazine, the results of the questionnaire, and the new positioning that produced the concept of "Being the Pride of Sundanese." The techniques used are photographic and vector techniques with the colors used are the colors of West Java (red, green, blue, brown) that are warm and bright.